Original researchA meta-analysis on the efficacy and tolerability of natalizumab in relapsing multiple sclerosis - Nikfar, Shekoufeh; Rahimi, Roja; Rezaie, Ali; Abdollahi, Mohammad (Archives of Medical Science, 2010)
Introduction: Natalizumab is a new humanized monoclonal antibody used in multiple sclerosis (MS). The aim of this meta-analysis was to evaluate the efficacy and tolerability of this drug in relapsing MS. PubMed, Scopus, Web of Science, and Cochrane Central Register of Controlled Trials were searched for studies that investigated the efficacy and/or tolerability of natalizumab in MS. Data were collected from 1966 to 2008 (up to October). Material and methods: The search terms were: “multiple sclerosis” or “MS” and “natalizumab”. “Mean change in Expanded Disability Status Scale (EDSS)”, “number of patients with at least one relapse”, and “number of patients with at least one new gadolinium (Gd)-enhancing lesion” were the key outcomes of interest for assessment of efficacy. “Any adverse events”, “serious adverse events”, “death”, and “withdrawal because of adverse events” were the key outcomes for tolerability. Among existing trials, four randomized placebo controlled clinical trials met our criteria and were included. Results: Pooled relative risk for at least one relapse in four trials including all doses was 0.7, with a non-significant RR (95% CI: 0.42-1.17, p = 0. 17). Summary RR for at least one relapse in two trials in which doses of 3 mg/kg or 6 mg/kg or 300 mg every 4 weeks were administered gave a value of 0.5 asa significant RR (95% CI: 0.42-0.61, p < 0.0001). The summary RR for at least one new Gd-enhancing lesion was 0.22, a non-significant RR (95% CI: 0.05-1.01, p = 0.051). Three deaths were reported in the natalizumab group. Comparing adverse events between natalizumab and placebo yielded a non-significant RR of 0.99 (95% CI: 0.96-1.01, p = 0.34) for any adverse events (n = 3), and a significant RR of 0.39 (95% CI: 0.29-0.52, p < 0.0001) for serious adverse events (n = 2). The summary RR for withdrawal due to adverse events by natalizumab vs. placebo therapy between two trials was 1.43, a non-significant RR (95% CI: 0.68-3.02, p = 0.35). Conclusions: It seems that using 3 or 6 mg/kg every 4 weeks is the best method of administration of natalizumab for preventing relapse and occurrence of new Gd-enhancing lesions. The current data on the efficacy and safety of natalizumab are insufficient to reach a convincing conclusion and thus further clinical trials are still needed.